Structural Characteristics and Inhibiting Oxidative Stress of Nine-steaming-nine-processing Polygonatum Kingianum Coll.et Hemsl Polysaccharides - LIU Yu-bin; CHEN Chang-an; SU Yi-lin; LUO Zhen; YAN Jin; LI Pan; DU Bing (Liang you shipin ke-ji)
This study investigated the structural characteristics and antioxidant activity of Polygonatum kingianum Coll.et Hemsl polysaccharides (NPKP) processed via nine-steaming-nine-drying methods. Monosaccharide composition analysis revealed that NPKP consists of rhamnose (3.5%), arabinose (4.6%), galactose (78.2%), glucose (2.1%), xylose (1.0%), mannose (1.3%), and galacturonic acid (9.4%). Molecular weight analysis revealed two main components in NPKP, with molecular weights of 196,857 Da and 13,653 Da. Methylation analysis indicated that NPKP is primarily linked by →4)-Glap-(1→ glycosidic bonds, accounting for 31.8% of the total, with a branching degree of 51.7%. Additionally, iodine-potassium iodide tests confirmed that NPKP is a highly branched polysaccharide. In vitro cellular experiments showed that NPKP significantly reduced reactive oxygen species (ROS) levels in HepG2 cells. It also upregulated antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH), alleviating oxidative stress induced by free fatty acids. Through these mechanisms, NPKP exhibited remarkable antioxidant capacity. This study provides a basis data for the application of Polygonatum polysaccharides as natural antioxidants and supports their role in mitigating oxidative stress-related diseases.